The Effect Of Catalyst Support On The Decomposition Of Methane To Hydrogen And Carbon. - Sharif Zein, Sharif Hussein; Mohamed, Abdul Rahman (2004)

(untitled)
Decomposition of methane into carbon and hydrogen over Cu/Ni supported catalysts was investigated. The catalytic activities and the lifetimes of the catalysts were studied. Cu/Ni supported on Ti02 showed high activity and long lifetime for the reaction. Transmission electron microscopy (TEM) studies revealed the relationship between the catalyst activity and the formation of the filamentous carbon over the catalyst after methane decomposition.